SCHOOL LOCATION AS CORRELATE OF STUDENT ACADEMIC PERFORMANCE. (Journal of Association of Educational Management and Policy Practitioners, 2025)
The study examined school location as correlate of students’ academic performance. The population of the study comprised of all students in the 45 public secondary schools in urban and rural Esan west local government area, Edo state...(346) students, selected through stratified random scrimping technique constituted the sample of this study. A descriptive research design was adopted. The instrument used for data collection was titled “students’ Academic performance in urban and rural public secondary school questionnaire. The t-test values of the variables were 66.96 and 63.56 respectively thus the result were found where found to be statistically significantly at the 0.05 level of significance. From the result of the funding, appropriate recommendation were made.